Health information post-encountering behaviours on social media platforms - Fallatah, Khalid U; Harvey, Morgan A; Rutter, Sophie (Information Research an international electronic journal, 2024)
Introduction. While much research has been done into how people encounter information, little has investigated post-encountering behaviours and their motivating factors. This exploratory study aims to study people’s behaviours after encountering health information on social media platforms. Method. Participants were recruited through the X platform (previously Twitter) by posting an invitation about the study. 39 participants from the UK took part in the diary study conducted from 3 June 2023 to 1 July 2023. Using their personal social media platforms, they submitted 71 diary entries of encountered health information through an online form. Analysis. Inductive content analysis (open coding) was used for the analysis. Results. The findings show that participants’ post-encountering behaviours consist of saving, sharing, directly using, discussing, exploring, ignoring, returning to browsing, and making mental notes of encountered health information. Our results indicate that participants are likely to experience emotional changes due to the influence of the health information they encounter. Findings also show that the influencing factors can be grouped into personal, informational, and health-related factors. Conclusions. This study provides insights into the nature of health information post-encountering behaviours on an everyday basis and their motivating factors. It also highlights the need for more in-depth investigations into the potential factors that moderate their relationships.